2023
DOI: 10.1177/03635465221147055
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of the Tönnis Grading System in Patients Undergoing Hip Preservation

Abstract: Background: The presence of pre-existing osteoarthritis (OA) has been associated with poor results after hip arthroscopic surgery. There is limited evidence validating the currently available grading systems of hip OA in patients undergoing hip preservation. Purpose/Hypothesis: Our purpose was to evaluate the interobserver and intraobserver reliabilities of 2 grading systems in a group of patients undergoing hip preservation: the Tönnis grading system and a simple 4-choice Likert scale. The hypothesis was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…18 Anteroposterior pelvis radiographs may also not provide the ideal radiographic view to assess joint degeneration. Magnetic resonance imaging to evaluate cartilage status may have been ideal, but this was logistically and fiscally impractical to accomplish; moreover, a recent study by Pullen et al 19 showed that magnetic resonance imaging scans demonstrated strong reliability in evaluating subchondral cysts but did not improve the interobserver variability of grading hip arthritis. Ideally, this study would have included more surgeons for generalizability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Anteroposterior pelvis radiographs may also not provide the ideal radiographic view to assess joint degeneration. Magnetic resonance imaging to evaluate cartilage status may have been ideal, but this was logistically and fiscally impractical to accomplish; moreover, a recent study by Pullen et al 19 showed that magnetic resonance imaging scans demonstrated strong reliability in evaluating subchondral cysts but did not improve the interobserver variability of grading hip arthritis. Ideally, this study would have included more surgeons for generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this is the most commonly used metric and is consistently evaluated from a medicolegal and billing documentation standpoint, it carries a variable interrater reliability ranging from 0.55 to 0.99 12 and has recently demonstrated moderate reliability in grading osteoarthritis. 18 Anteroposterior pelvis radiographs may also not provide the ideal radiographic view to assess joint degeneration. Magnetic resonance imaging to evaluate cartilage status may have been ideal, but this was logistically and fiscally impractical to accomplish; moreover, a recent study by Pullen et al 19 showed that magnetic resonance imaging scans demonstrated strong reliability in evaluating subchondral cysts but did not improve the interobserver variability of grading hip arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative variables recorded for each patient included age, sex, affected side, weight, height, body mass index (BMI), visual analogue scale (VAS 0–100 mm), joint space based on the Tönnis classification [29], cartilage injury degree based on the modified acetabular labrum articular disruption (ALAD) [22], modified Harris hip score (mHHS) [16], hip outcome score activities of daily living and sport‐scale (HOS‐ADL, HOS‐SS) [34], and the Western Ontario and McMaster index (WOMAC) [37]. For those patients who required conversion to THA, time from arthroscopy to reintervention for THA was also recorded.…”
Section: Methodsmentioning
confidence: 99%